A model for evaluating water distribution system capacity as a function of the total pipeline length - Loubser, Carlo; Grotepass, Frans; Jessica May Winter; Heinz Erasmus Jacobs (Journal of water supply : research and technology - AQUA, 2023)
Planners are often faced with the challenge to provide crude estimates of water distribution system (WDS) infrastructure capacity and associated costs in the early phases of greenfield developments. This study investigated the relationship between the physical and hydraulic characteristics of a WDS and the corresponding serviced area. Five physical parameters (a) and two hydraulic parameters (b) describing the serviced area were identified for analysis, namely (a) total pipeline length, land area, area shape factor, terrain index, reservoir distance from area centroid and (b) peak flow rate and average static system pressure. Multiple linear regression was performed on the data. A model was compiled linking the total pipeline length of a WDS to the peak flow rate. The model is applicable to predominantly residential service zones larger than 80 hectares with a peak hour flow rate of